Micrometeorology - Foken, Th (Springer, 2017)
The book focusses on atmospheric processes, which directly affect human environments within the lowest 100?1000 meters of the atmosphere over regions of only a few kilometres in extent. The book is the translation into English of the third edition of the German book "Applied Meteorology? Micrometeorological Methods". It presents, with selected examples, the basics of micrometeorology applied to disciplines such as biometeorology, agrometeorology, hydrometeorology, technical meteorology, environmental meteorology, and biogeosciences. The important issues discussed in this book are the transport processes and fluxes between the atmosphere and the underlying surface. Vegetated and heterogeneous surfaces are special subjects. The author covers the areas of theory, measurement techniques, experimental methods, and modelling all in ways that can be used independently in teaching, research, or practical applications.